Akuntabilitas dan Transparansi Pengelolaan ZIS FEBI IAIN Surakarta - Latifah Nur Baiti (Academica: Journal of Multidisciplinary Studies, 2018)
This research aims to know the ZIS effort in realizing the accountability and transparency of management of zakat funds. With a qualitative descriptive approach, the data in this study was obtained by the interview method of the Chairman and the ZIS member of the Faculty of Economics and Business of Islam (FEBI). Literature studies are also conducted to enrich the discussion of research results. The results showed that ZIS manager at FEBI has sought to realize accountability and transparency of fund management in the form of publication of receipts and distribution reports and Zakat, Infak, and charity. In addition, ZIS in FEBI has also channeled zakat, Infak, and charity funds to various social organisations.Keywords: accountability, transparancy, zakat